FAKTOR-FAKTOR PENENTU AUDIT DELAY DI INDONESIA: STUDI META ANALYSIS - Handarudigdaya JK; Tri Wdiyastuti; Adi Wiratno; Iskandar Ahmaddien (Jurnal Teknologi dan Terapan Bisnis, 2019)
This study aims to examine the determinants of audit delay in Indonesia, using Meta Analysis. Where Meta analysis is a standard statistical method that serves to synthesize results from individual studies that have "same" themes in order to provide a more significant answer (Cooper, 2010). The sample in this study using 35 study (articles, working papers, theses) obtained from google scholar from 2008-2018 obtained from google scholar, and selected by purposive sampling. Each selected scientific publication must have the same concept and definition, both dependent and independent variables. The results of empirical testing with Meta Analysis found that ROA, DER, DR, Auditor Opinion, Profit / Loss, and Age of Company is the determinant of audit delay. While Total Assets and Auditor Reputation is not a determinant factor audit delay